Sistematización de la práctica pedagógica realizada en el 2023, con los integrantes del grupo infantil de la escuela de formación Danza Kapital para desarrollar estrategias didácticas que implementen la mímesis y la exploración como formas de aprendizaje para la danza de la cumbia. - Solorza Nieto, Nataly (Universidad Antonio Nariño, 2024)
The main objective of this degree project is to systematize the experiences of pedagogical practices 1 and 2, carried out in 2023 with the children of the Foundation Artistic Cultural Kapital Dance. We focus specifically on finding strategies that integrate mimesis and exploration into the teaching and learning of dance of the Colombian Cumbia